Pentingnya Peningkatan Pelayanan Untuk Nasabah Melalui Pembiayaan Tanpa Bunga Di Bank Muamalat Probolinggo - Agus Wiastono (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2020)
This study aims to determine the strategy of developing financing products in an effort to increase the capacity of micro, small and medium enterprises (MSMEs) at Islamic people’s financing bank (BANK) MUAMALAT in Probolinggo . This type of research uses qualitative methods. Data sources used in this study are primary data and secondary data. Data collection techniques used were interviews and documentation. The results of this study ate the existence of BANK MUAMALAT in Probolinggo is very beneficial for the community especially thosr who have small an medium micro businesses because with the financing can help in terms of capital, increase the capacity to trade and help sustain the economy in Probolinggo .